Legal uncertainty: A selective deterrent - Matthias Lang (Max Planck Institute for Research on Collective Goods, 2014)
I show that legal uncertainty, i.e., uncertainty about the legality of a specific action, has positive welfare effects. Legal uncertainty works as a screening device provided that the threshold of legality is uncertain. The uncertainty discourages controversial actions, while it encourages socially beneficial actions. Legal uncertainty is a selective deterrent, because the uncertainty changes the probability of being convicted in opposite directions. Hence, in designing optimal rules there is no reason to avoid legal uncertainty at all costs. For example, the positive effect of legal uncertainty influences the balance between per-se rules and rules of reason in competition law.
Keywords: K2; D8; K4; L5; 330; regulation; asymmetric information; deterrence; enforcement; legal uncertainty; rules of reason